ASUHAN KEPERAWATAN PADA PASIEN CA MAMMAE POST OPERASI MASTEKTOMI DENGAN INTERVENSI HAND MASSAGE TERHADAP INTENSITAS NYERI DI RUANG ANGGREK C RSUD KABUPATEN TANGERANG - Eli Mantika; Cicirosnita Jayadi Idu; Ahmad Hambali (Yayasan Nusantara Hasana Berdikari, 2024)
Breast cancer ranks first in terms of the highest number of cancers in Indonesia and is one of the first contributors to death due to cancer. One of the physical complaints that many patients complain about is pain. Pain is a painful experience for them and they need to be given pharmacological and non-pharmacological therapy to reduce its intensity. Objective to obtain an overview of nursing care for ca mammae patients with hand massage intervention on pain intensity at the Tangerang District Hospital. This research is a case study and is combined with a pre-experiment using a paired sample t-test. The results of the analysis showed a significant change in the intensity of pain experienced by patients before and after hand massage therapy (p-value=0.015). The patient reported being more relaxed and reducing the pain. Judging from the objective response, the patient appeared less anxious, grimaced in pain and calmer than before.